PTU-042 DNA-PK or ATM inhibition inhibits non-homologous end joining and enhances chemo- and radio sensitivity in hepatocellular cancer cell lines. (28th May 2012) - Cornell, L; Munck, J; Curtin, N; Reeves, H
Abstract : Introduction: Hepatocellular carcinoma (HCC) is chemotherapy resistance possibly due to dysregulation of DNA damage signalling and repair. DNA double-strand breaks (DSBs) are the most cytotoxic lesions induced by ionising radiation (IR) and anticancer drugs such as topoisomerase II poisons (eg, doxorubicin). DSBs are repaired by non-homologous end joining (NHEJ), initiated by DNA-dependent protein kinase (DNA-PK), and homologous recombination (HR), reportedly initiated by Ataxia telangiectasia mutated (ATM). DNA-PK is up-regulated in HCC (GEO profiles), possibly contributing to anticancer therapy resistance. To assess DNA-PK and ATM as therapeutic targets for chemo- and radio-sensitisation in HCC we determined the effect of their inhibition in HCC cell lines. Methods: DNA-PK and ATM protein levels and activation by IR (Western blot), DSB levels (y-H2AX foci), HR (RAD51 foci), cell growth (DAPI fluorescence) and cytotoxicity (colony formation) following exposure to IR or doxorubicin was determined in a panel of 6 hepatoma cell lines (HepG2, Hep3B, Huh7, SNU-182, SNU475 and PLC/PRF/5). Studies were performed in the presence and absence of the DNA-PK inhibitor NU7441, and the ATM inhibitor KU55933. Results: DNA-PK protein concentration and activity were high in all HCC cell lines. In contrast, ATM expression varied, and was lowest in Hep3B cells. Cell-specific sensitivities to IR and doxorubicin correlated with ATM expression (highest in HepG2 and lowest in Hep3B). NU7441 sensitised all cells to doxorubicin (average PF50 4.3±3.0) and IR (average PF50 3.9±1.1), significantly increasing growth inhibition and reducing survival (4.8 to 3.3-fold; colony forming assays). KU55933 significantly potentiated cytotoxicity in HepG2 cells (eightfold) but had little effect on cytotoxicity in Hep3B cells. Following exposure to IR, both NU7441 and KU55933 delayed DSB repair (∼50% clearance yH2AX foci at 4 h vs only 10%–15% in presence NU7441). NU7441 also enhanced HR (threefold increase in RAD51 foci), while KU55933 had little effect. Conclusion: DNA-PK levels were high in all HCC cells and its inhibition with NU7441 was associated with significant chemo- and radio-sensitisation. Potentiation by ATM inhibition varied in the cell lines, reflecting the level of ATM expression. Both inhibitors substantially impaired the rapid phase of DNA repair commonly attributed to NHEJ. Notably, KU55933 had little effect on HR, suggesting that ATM is not central to this repair pathway. We propose that these inhibitors will increase the effectiveness of lower safer doses of cytotoxic therapies, amplifying tumour toxicity, and that DNA-PK and ATM levels in tumour and non-tumour liver will predict those patient likely to benefit. Competing interests: None declared.